Enabling High-Energy, High-Voltage Lithium-Ion Cells: Standardization of Coin-Cell Assembly, Electrochemical Testing, and Evaluation of Full Cells. Issue 14 (9th November 2016) - Long, Brandon R.; Rinaldo, Steven G.; Gallagher, Kevin G.; Dees, Dennis W.; Trask, Stephen E.; Polzin, Bryant J.; Jansen, Andrew N.; Abraham, Daniel P.; Bloom, Ira; Bareño, Javier; Croy, Jason R.
Abstract : Coin-cells are often the test format of choice for laboratories engaged in battery research and development as they provide a convenient platform for rapid testing of new materials on a small scale. However, reliable, reproducible data via the coin-cell format is inherently difficult, particularly in the full-cell configuration. In addition, statistical evaluation to prove the consistency and reliability of such data is often neglected. Herein we report on several studies aimed at formalizing physical process parameters and coin-cell construction related to full cells. Statistical analysis and performance benchmarking approaches are advocated as a means to more confidently track changes in cell performance. We show that trends in the electrochemical data obtained from coin-cells can be reliable and informative when standardized approaches are implemented in a consistent manner.